Donor sperm insemination after failed intra-couple intracytoplasmic sperm injection. (4th March 2018) - Hennebicq, Sylviane; Blagosklonov, Oxana; Eustache, Florence; Papaxanthos, Aline; Drouineaud, Veronique; Guillemain, Catherine; Mirallie, Sophie; Delepine, Beatrice; Rives, Nathalie; Berthaut, Isabelle; Frapsauce, Cynthia; Guérin, Jean-François; et al.
ABSTRACT: The purpose of the present multicenter study was to investigate whether an artificial insemination with donor sperm (AID) procedure after intra-couple intracytoplasmic sperm injection (ICSI) failure offers a significant chance of pregnancy and to identify prognostic factors for pregnancy after an AID procedure. An eleven-year retrospective multicenter study was conducted among 13 Centre d'Etude et de Conservation des Oeufs et du Sperme (CECOS) centers. A total of 319 couples having undergone an AID procedure after intra-conjugal ICSI failure were included in this study; a total of 1, 159 AID and 1, 011 intra-conjugal ICSI cycles were performed. Among the prognostics parameters, the parity and the embryo quality could not be adequately addressed, therefore the parity was not included in the statistical analysis and the embryo quality has been presented as preliminary observations . The pregnancy rate per cycle was 12.0% (139/1, 159) and the overall AID pregnancy rate per couple was 43.6% (139/319). Normal or oligoasthenoteratozoospermia (OAT) semen and women aged 34 years or above at the time of AID procedure obtained the lowest AID clinical pregnancy rate. Azoospermia or cryptozoospermia semen and women aged below 34 years obtained the highest AID clinical pregnancy rate. In conclusion, the transition to the AID procedure after intra-conjugal ICSI failure allows such couples to obtain a pregnancy, however after each ART failure AID transition should be proposed according to the woman's age and sperm characteristics. Abbreviations : AID: artificial insemination with donor sperm; ICSI: intracytoplasmic sperm injection; CECOS: Centre d'Etude et de Conservation des Oeufs et du Sperme; OAT: oligoasthenoteratozoospermia; IVF: in vitro fertilization; ART: artificial reproductive technology; β hCG: beta human chorionic gonadotrophin; SD: standard deviation; OR: Odds ratio